Guide to race equality in FE - Ainley, Beulah (Essential FE toolkit series, 2006)
"This guide shows how managers in FE can meet the challenges of promoting equality and diversity in their colleges. Beulah Ainley examines best-practice examples, discusses how to ensure the equality scheme remains effective throughout the college, considers the importance of good race relations, and looks at how to provide appropriate services to meet the needs of a diverse range of students."--BOOK JACKET.